H19 lncRNA alters stromal cell growth via IGF signaling in the endometrium of women with endometriosis. Issue 8 (18th June 2015) - Ghazal, Sanaz; McKinnon, Brett; Zhou, Jichun; Mueller, Martin; Men, Yi; Yang, Lihua; Mueller, Michael; Flannery, Clare; Huang, Yingqun; Taylor, Hugh S
Abstract: Endometriosis affects approximately 15% of reproductive aged women and is associated with chronic pelvic pain and infertility. However, the molecular mechanisms by which endometriosis impacts fertility are poorly understood. The developmentally regulated, imprinted H19 long noncoding RNA (lncRNA) functions to reduce the bioavailability of microRNA let‐7 by acting as a molecular sponge. Here we report that H19 expression is significantly decreased in the eutopic endometrium of women with endometriosis as compared to normal controls. We show that decreased H19 increases let‐7 activity, which in turn inhibits Igf1r expression at the post‐transcriptional level, thereby contributing to reduced proliferation of endometrial stromal cells. We propose that perturbation of this newly identified H19/Let‐7/IGF1R regulatory pathway may contribute to impaired endometrial preparation and receptivity for pregnancy in women with endometriosis. Our finding represents the first example of a lncRNA‐based mechanism in endometriosis and its associated infertility, thus holding potential in the development of novel therapeutics for women with endometriosis and infertility. Synopsis: Endometriosis is associated with infertility in reproductive aged women, but the molecular mechanism is unknown. H19 is a long noncoding RNA that is normally expressed in eutopic endometrium and shown here to play a role in endometrial stromal cell growth via the microRNA let‐7 and its downstream target IGF1R . H19 expression is decreased in the eutopic endometrium of women with endometriosis compared to women without endometriosis. Decreased H19 expression leads to increased activity of let‐7, which inhibits IGF1R expression at the post‐transcriptional level. Reduced IGF1R activity leads to impaired endometrial stromal cell proliferation and may impact endometrial receptivity for pregnancy. Aberrations in this H19/let‐7/IGF1R regulatory pathway in women with endometriosis may represent one potential mechanism for infertility in this patient population. Abstract : Endometriosis is associated with infertility in reproductive aged women, but the molecular mechanism is unknown. H19 is a long noncoding RNA that is normally expressed in eutopic endometrium and shown here to play a role in endometrial stromal cell growth via the microRNA let‐7 and its downstream target IGF1R .